Two new species of Teagueia (Orchidaceae: Pleurothallidinae) from East-Central Ecuador - Jost, Lou (2011)
Two new species of Teagueia, T. barbeliana and T. puroana, are described and illustrated. Their relationship to other Teagueia, their scientific importance, and their conservation is discussed. Closest relatives are T. alyssana, T. sancheziae, T. cymbisepala, and T. jostii, and like them, the new species are high- elevation (>3100m) endemics of the upper Río Pastaza watershed in the eastern Andes of Ecuador. Teagueia barbeliana differs from its relatives by broad rounded flower parts, lateral sepals connate for half their length, column apex winged. Teagueia puroana differs from relatives by its long-acuminate petals and sepals.